2022
DOI: 10.1111/jvh.13660
|View full text |Cite
|
Sign up to set email alerts
|

Global prevalence of occult hepatitis B: A systematic review and meta‐analysis

Abstract: The study aimed to investigate the prevalence and risk factors associated with occult hepatitis B virus (HBV) infection (OBI) in the global population. We searched PubMed, Embase, CINAHL, Cochrane and Web of Science from database inception through 27 Dec, 2018. Studies reporting HBV‐DNA serological data in previously undiagnosed hepatitis B patients were included. The data were further categorized according to the presence of risk factors. After an initial screening of 2,325 records, we finally included 98 art… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 69 publications
(99 reference statements)
0
9
0
Order By: Relevance
“…Interestingly, some studies have shown an association between transaminase elevation and the reappearance of serum HBV DNA in chronic hepatitis C patients, suggesting a possible impact of such transitory HBV reactivation on hepatocyte necrosis [6,7]. A similar, negative impact of OBI on the progression of CLD has been shown in patients with alcoholic or cryptogenic liver disease and-recently-also in patients with NAFLD [72,88,89,130,131]. In particular, one study assessed the presence of HBV viral genomes in liver tissues collected from HBsAg-negative morbidly obese patients at the time of bariatric surgery, revealing a prevalence of about 13% of OBI, which was an independent predictor of NASH and fibrosis in these subjects [89].…”
Section: Obi and Chronic Liver Diseasementioning
confidence: 73%
See 1 more Smart Citation
“…Interestingly, some studies have shown an association between transaminase elevation and the reappearance of serum HBV DNA in chronic hepatitis C patients, suggesting a possible impact of such transitory HBV reactivation on hepatocyte necrosis [6,7]. A similar, negative impact of OBI on the progression of CLD has been shown in patients with alcoholic or cryptogenic liver disease and-recently-also in patients with NAFLD [72,88,89,130,131]. In particular, one study assessed the presence of HBV viral genomes in liver tissues collected from HBsAg-negative morbidly obese patients at the time of bariatric surgery, revealing a prevalence of about 13% of OBI, which was an independent predictor of NASH and fibrosis in these subjects [89].…”
Section: Obi and Chronic Liver Diseasementioning
confidence: 73%
“…The worldwide epidemiology of OBI is quite variable, as it depends on many factors, such as the sensitivity of HBsAg and HBV DNA assays, whether there are risk factors for HBV exposure, the prevalence of HBV among the general population in the various geographic areas, the anti-HBV vaccination programs in the different countries, and the presence and severity of liver disease in the examined populations [ 71 , 72 ]. Indeed, most of the studies concerning OBI prevalence have been carried out on blood donors and on patients with liver disease; thus, they are not truly representative of the general population.…”
Section: Epidemiology Of Obimentioning
confidence: 99%
“…Health management after HBsAg loss is still very important for those populations. In addition, as HBV cannot be completely eradicated because of the persistence of covalently closed circular DNA (cccDNA) and integrated HBV DNA, another important consideration is occult HBV or HBV reactivation [ 17 , 18 ]. Occasionally, occult HBV or HBV reactivation may be mild or even asymptomatic, which results in occult HBV or HBV reactivation being easily neglected in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…However, it is important to point out that these data are largely derived from studies on Chinese populations, which may not be predictive of the OBI prevalence in Vietnam. Low levels of OBI could also be due to the sensitivity of the HBsAg test used, or good health care that reduces the risk of OBI transmission [32,33]. Furthermore, regionality and socioeconomic status have been shown to influence the discrepancy in HBV infections and OBI rates between populations [34].…”
Section: Discussionmentioning
confidence: 99%